(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The populations of the slums are increasing day by day at an alarming rate due to the urbanization of the country. The living condition in the slum area is very low. Generally slums are lacking from access to safe water, drainage and sanitation facilities and basic health care facilities. The study has been carried out to assess the present conditions of the water supply and sanitation of the Karail slum of Dhaka city. The research work was carried out by using Participatory Rural Appraisal tools including Focus Group Discussion, Key Informant Interview and Household Survey. Poor physical environment with non-existent solid waste disposal system is very common phenomenon in Surveyed slum. Most of the people of the slum live under unhygienic environment. However, the level of hygiene knowledge and practice has been found to be significantly low among the Karail slum dwellers. The study in Karail area of Dhaka city has found that the sanitary and water supply conditions are improving very slowly. Comprehensive and sustained wastewater management in combination with sanitation and hygiene is central to good health, food security, and economic development for the slum people. J. Environ. Sci. & Natural Resources, 8(1): 161-163 2015